2012
DOI: 10.1186/1471-2172-13-28
|View full text |Cite
|
Sign up to set email alerts
|

Significance of decoy receptor 3 (Dcr3) and external-signal regulated kinase 1/2 (Erk1/2) in gastric cancer

Abstract: BackgroundDecoy receptor 3 (DcR3), a member of the tumor necrosis factor receptor (TNFR) superfamily, is associated with anti-tumor immunity suppression. It is highly expressed in many tumors, and its expression can be regulated by the MAPK/MEK/ERK signaling pathway. The MAPK/MEK/ERK pathway has been reported to be a regulator in tumor occurrence, development and clonal expansion. External-signal regulated kinase (ERK) is a vital member of this pathway.ResultsThe expression of DcR3 and ERK1/2 in tumor tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The results indicated that TIPE was expressed in the cytoplasm and nucleolus of GC cells, and that TIPE mRNA expression was significantly increased in GC compared with normal gastric tissues. The results were consistent with a previous finding that TIPE is overexpressed in human malignant tumors (8)(9)(10)14). However, no association was observed between TIPE mRNA expression and nodal status or differentiation in the present study.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The results indicated that TIPE was expressed in the cytoplasm and nucleolus of GC cells, and that TIPE mRNA expression was significantly increased in GC compared with normal gastric tissues. The results were consistent with a previous finding that TIPE is overexpressed in human malignant tumors (8)(9)(10)14). However, no association was observed between TIPE mRNA expression and nodal status or differentiation in the present study.…”
supporting
confidence: 82%
“…The overexpression of DcR3 in tumor cells protects the cells from apoptosis (13). Therefore, DcR3 and ERK are vital in the development of GC (14).…”
Section: Introductionmentioning
confidence: 99%
“…Cells were incubated with 25 ng/ml sFasL and/or 5 mg/ml IgG, 5 mg/ml rDcR3, 50 mM PD098059 for 24 h. (C) Phosphorylation of ERK1/2 was analyzed by Western blot. Cells were incubated with 25 ng/ml sFasL and/or 5 mg/ml IgG, 5 mg/ml rDcR3, 50 uM PD098059 for 24 h. [34,35]. We found that DcR3 promoted ERK1/2 phosphorylation, but did not affect the Akt pathway.…”
Section: Tl1aedr3 and Lightelymphotoxin B Receptor Interactionsmentioning
confidence: 98%
“…DcR3 has been found to be highly expressed in many malignant tumors 2023. Silencing of DcR3 can affect the proliferation, invasion, and metastasis ability of tumor cells and sensitize tumor cells to Fas-mediated apoptosis 24,25.…”
Section: Introductionmentioning
confidence: 99%